A versatile and recycled pigment foam coloring approach for natural and synthetic fibers with nearly-zero pollutant discharge. (10th January 2020) - Chen, Shaoyu; Fei, Liang; Ge, Fangqing; Liu, Jingyan; Yin, Yunjie; Wang, Chaoxia
Abstract: To sustain an ecological and economical textile industry, the development of a simple coloring process, featuring characteristics of both minimum pollutant discharge and versatile for natural and synthetic fibers, remains a challenging task. Herein, a simple (only containing coloring and curing process) and recycled pigment foam coloring approach for cotton, silk and polyester is designed, which is based on photoresponsive foams formed by a nonionic azobenzene surfactant (NAS ) doping into a pigment foam coloring system containing sodium dodecyl sulfate (SDS), pigment dispersion and binder. Detailed investigations of photoisomerization of NAS, foam properties and color parameters of the obtained fabrics in the recycled pigment foam coloring system are presented. In the pigment foam coloring system, NAS maintains highly selective and reversible photoisomerization properties, allowing to generate colored photoresponsive foams with high photochemical fatigue resistance. With a tunable stability controlled by light, the stable colored foams can be applied in the coloring process for cotton, silk and polyester, while the rapid breakage of residual foams triggered by UV-light enables the recycling of residual foams for further re-utilization at the end of the coloring process, providing a simple alternative coloring process for natural and synthetic fibers with nearly-zero pollutant discharge. This could open up a promising strategy to improve the ecological and economic efficiency of textile coloring industry. Graphical abstract: Image 1 Highlights: A nonionic azobenzene surfactant has been designed to prepare photoresponsive foams. The stability of colored foams can be remotely controlled solely by light. The process is feasible in coloring cotton, silk and polyester fabrics. Residual foams are recyclable, enabling the process to be nearly-zero pollutant discharge.